2022
DOI: 10.1002/phar.2658
|View full text |Cite
|
Sign up to set email alerts
|

Use of naldemedine is associated with reduced incidence of hyperactive delirium in cancer patients with opioid‐induced constipation: A nationwide retrospective cohort study in Japan

Abstract: Background Medical benefits of peripherally acting mu‐opioid receptor antagonists other than improving opioid‐induced constipation remain unclear. Our aim was to evaluate the association between the use of naldemedine and incidence of hyperactive delirium in cancer patients receiving chemotherapy and opioid therapy. Methods We conducted a propensity score‐matched analysis using a nationwide inpatient database in Japan. Cancer patients receiving both inpatient chemotherapy and opioid therapy from June 1, 2017, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…In a retrospective study, it has been reported that naldemedine can reduce hospital costs and hospital stays by reducing the incidence of hyperactive delirium [ 28 ]. In the present study, the total medical costs six months after opioid initiation were low in the naldemedine arm compared to the magnesium oxide arm in the non-early prescription group, but not in the early prescription group.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, it has been reported that naldemedine can reduce hospital costs and hospital stays by reducing the incidence of hyperactive delirium [ 28 ]. In the present study, the total medical costs six months after opioid initiation were low in the naldemedine arm compared to the magnesium oxide arm in the non-early prescription group, but not in the early prescription group.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] In addition, there are many adverse reactions caused by general anesthetics, especially nausea and vomiting, constipation, hypotension, respiratory depression and hyperalgesia caused by opioids. [21][22][23][24] There are few data currently available from published studies that compared peripheral nerve blocks with general anesthesia for patients who underwent DF surgery. To compare the effects of the above two different anesthesia methods on the perioperative physiological function of patients, this study intends to prospectively analyze the impact of general anesthesia versus peripheral nerve block anesthesia on perioperative hemodynamic changes and the prognosis of diabetic patients to evaluate the beneficial and detrimental effects of the two different anesthesia methods on patients.…”
Section: Introductionmentioning
confidence: 99%
“… 18–20 In addition, there are many adverse reactions caused by general anesthetics, especially nausea and vomiting, constipation, hypotension, respiratory depression and hyperalgesia caused by opioids. 21–24 …”
Section: Introductionmentioning
confidence: 99%